The Use of Passives and Impersonal Style in Civil Engineering Writing. (January 2018) - Conrad, Susan
Claims abound about passives and the impersonal style they create. Few studies, however, check the claims with a large, systematic analysis of texts from either academia or industry. Motivated by the need to teach effective workplace writing skills to undergraduate engineering students, this study investigates the use of passives and associated impersonal style features in 170 practitioner reports, journal articles, and student reports from civil engineering. Using multidimensional analysis (a technique from corpus linguistics) and interviews of practitioners, students, and faculty, the study found that, as expected, engineering texts, compared to nontechnical texts, have a frequent use of impersonal style features; however, they use passives for a wider range of functions than is typically described in technical writing literature. Furthermore, compared to the journal articles and student reports, the practitioner reports use significantly fewer features of impersonal style. The findings inform teaching materials that present a more realistically complex picture of the language structures and functions important for civil engineering practice.